Solve the simultaneous equations: y=x+1, x^2+y^2=13

We already have an expression for y, so we can substitute this in:x2+(x+1)2=x2+(x+1)(x+1) = x2+x2+2x+1=2x2+2x+1 and hence 2x2+2x+1=13 and so 2x2+2x-12=0Now look for common factors. Here we can take out a factor of 2 to get2(x2+x-6)=0And we can use method to factorise to 2(x-2)(x+3) = 0So setting expressions to 0 we have x=2 or x=-3.Substitute values back into expression for y to obtainy = x+1 = 2+1 = 3 or y = -3+1 = -2

Answered by Lauren C. Maths tutor

6115 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Let X be a normally distributed random variable with mean 20 and standard deviation 6. Find: a) P(X < 27); and b) the value of x such that P(X < x) = 0.3015.


y = (x^3)/3 - 4x^2 + 12x find the stationary points of the curve and determine their nature.


Sine Rule


Integral of Cosec(x)/Sec(x) (i.e. Use of trignometric identities)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences